Polycrystalline alumina fiber and preparation method thereof
By using sol-gel method and centrifugal filament throwing technology on alumina fibers, and depositing boron nitride nanolayers on their surfaces, the problems of grain coarsening and mechanical properties of alumina fibers at high temperatures are solved, and better high-temperature heat insulation and mechanical properties are achieved.
Patent Information
- Application Number
- CN202510294581.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
Alumina fibers are prone to grain coarsing, inelastic deformation and mechanical properties at high temperatures, and their fiber strength decreases in corrosion atmospheres, limiting their application in thermal protection and aerospace fields.
Crystalline aluminum chloride and aluminum powder are used as aluminum sources, tartaric acid, nitric acid and lactic acid are used as stabilizers and spinning additives, ethyl orthosilicate is used as silicon source, and zirconium-containing solution is used as reinforcement additives. The fiber blank is formed by sol-gel method and centrifugal filament throwing technology, and boron nitride nanolayers are deposited on the fiber surface by heat treatment and chemical vapor deposition method to prepare polycrystalline alumina fibers.
It effectively inhibits grain growth, improves the high-temperature thermal insulation and mechanical properties of the fiber, enhances the oxidation resistance and interface bonding strength, and improves the storage and thermal insulation stability of the fiber.
Smart Images

Figure CN119797896A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber materials, and in particular relates to a polycrystalline alumina fiber and a preparation method thereof. Background Art
[0002] Alumina fiber is a polycrystalline inorganic fiber whose main component is alumina, and its main component is α-Al2O3. Alumina fiber is one of the new ultra-light high-temperature thermal insulation materials at home and abroad. It can be made into a colloidal solution with a certain viscosity by the "sol-gel" method, and the solution is spun into a fiber embryo by high-speed centrifugation, and then transformed into Al-Si alumina polycrystalline fiber through processes such as dehydration, drying and medium-high temperature heat treatment and crystallization. It can be used as a high-temperature thermal insulation material, a catalyst or catalyst carrier for high-temperature reactions, and a reinforcement for metal-based, ceramic-based and other composite materials. It has a wide range of applications in aerospace, mechanical and chemical industries.
[0003] Alumina fibers are relatively brittle, and the fiber grain boundaries easily become channels for oxygen diffusion at high temperatures, resulting in grain coarsening and inelastic deformation, which affects their performance stability. At the same time, when the insulation temperature is increased or in a water vapor environment, the degree of alumina fiber grain coarsening is aggravated, resulting in a significant decrease in the mechanical properties of the fiber. The high-porosity fiber aggregate composed of fiber accumulation has strong hygroscopicity, which affects its storage and thermal insulation stability. In addition, in a corrosive atmosphere, especially above 1000°C, the fiber strength of alumina fibers gradually decreases with the increase of temperature, which seriously restricts their application in many cutting-edge fields such as thermal protection and aerospace. Summary of the invention
[0004] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide a polycrystalline alumina fiber and a preparation method thereof, using crystalline aluminum chloride and aluminum powder as aluminum sources, tartaric acid, nitric acid and lactic acid as stabilizers and spinning aids, tetraethyl orthosilicate as a silicon source, and a zirconium-containing solution as a reinforcing aid. A sol-gel method and a centrifugal spinning technology are used to form a fiber blank. After the fiber blank is heat-treated and sintered, a boron nitride nanolayer is deposited on its surface by chemical vapor deposition to prepare polycrystalline alumina fiber.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing polycrystalline alumina fiber comprises the following steps: S1. Take crystalline aluminum chloride and add deionized water to mix evenly, then add a mixed solution of aluminum powder, tartaric acid, nitric acid and lactic acid, heat and reflux at 80-100°C for 2-4h to obtain a polyaluminum chloride mother liquor; S2, mixing basic zirconium carbonate, glacial acetic acid and ethanol evenly to obtain a zirconium-containing solution, mixing the polyaluminium chloride mother solution, the zirconium-containing solution and tetraethyl orthosilicate evenly, then adding a fiber-forming aid, and concentrating by vacuum distillation to obtain a spinning colloid; S3, spinning the spinning colloid by centrifugal spinning machine, the spinning colloid forms fiber blanks under the secondary traction of centrifugal force and hot air flow, and the fiber blanks are collected by a fiber forming hood; S4. After the fiber blank is dried, it is heat-treated, and a boron nitride nanolayer is deposited on the surface of the heat-treated and sintered alumina fiber using a chemical vapor deposition method to prepare the polycrystalline alumina fiber.
[0006] Preferably, the molar ratio of the aluminum powder, tartaric acid, lactic acid, nitric acid and tetraethyl orthosilicate is 1: 0.3-0.5: 0.6-0.7: 0.3-0.4: 0.15-0.3.
[0007] Preferably, the mass ratio of basic zirconium carbonate, glacial acetic acid and ethanol is 2.5-3:2-2.5:7-10.
[0008] Preferably, the fiber-forming aid is polyvinyl pyrrolidone.
[0009] Preferably, the viscosity of the spinning colloid is 40-80 Pa·s.
[0010] Preferably, the process parameters of the heat treatment are as follows: heating to 500-550°C at a rate of 1-3°C / min, keeping warm for 0.5-1h, then heating to 600-800°C at a rate of 3-5°C / min, keeping warm for 0.5-1h, then heating to 1000-1400°C at a rate of 5-10°C / min, keeping warm for 1-1.5h.
[0011] Preferably, the process parameters of the chemical vapor deposition method are as follows: boron trichloride and ammonia are used as reaction gas sources, argon is used as carrier gas and dilution gas, the flow rate ratio of ammonia, boron trichloride and argon is 3:1:5, the reaction system pressure is 5KPa, the deposition temperature is 950~1050℃, and the deposition time is 45~60min.
[0012] Preferably, during the centrifugal spinning process in step S3, the spinning disk has a rotation speed of 5000-6000 r / min.
[0013] Preferably, the temperature in the fiber-forming hood is controlled at 50-70° C., and the relative humidity is 30-50%.
[0014] A polycrystalline alumina fiber is made by the preparation method as described above.
[0015] Beneficial effects of the present invention: The invention adopts crystalline aluminum chloride and aluminum powder as aluminum sources, tartaric acid, nitric acid and lactic acid as stabilizers and spinning aids, tetraethyl orthosilicate as silicon source, zirconium-containing solution as reinforcing aid, adopts sol-gel method and centrifugal spinning technology to form fiber blank, and adopts chemical vapor deposition method to deposit boron nitride nanolayer on the surface of fiber blank after heat treatment and sintering to prepare polycrystalline alumina fiber, wherein silicon dioxide is introduced in the form of tetraethyl orthosilicate to inhibit grain growth, and zirconium-containing solution is prepared with basic zirconium carbonate, glacial acetic acid and ethanol as raw materials, and is doped into polyaluminum chloride mother liquor to enhance the resistance of alumina fiber. High-temperature thermal insulation, and the lattice distortion caused by Si-O-Zr increases the overall configuration entropy of the fiber, which can increase the activation energy of grain growth and inhibit its crystallization. Boron nitride has a multilayer lamellar structure, good interface bonding strength, and good antioxidant properties. Its oxidation starting temperature is relatively high, and it forms a protective condensed oxide boron trioxide at high temperatures, which covers and fills the voids in the alumina fiber, inhibiting the migration and diffusion of oxygen, thereby maintaining the passivation of the alumina fiber, and can eliminate internal pore structures such as pores to avoid becoming stress concentration points. When the fiber is subjected to external loads, it can prevent crack propagation. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 This is a SEM image of the polycrystalline alumina fiber prepared in Example 1 of the present invention after being treated with water vapor, alkaline vapor and acid vapor for 24 hours.
[0018] Among them, a is the SEM image after 150°C water vapor treatment for 24 hours, b is the SEM image after sodium nitrite alkaline vapor treatment for 24 hours, and c is the SEM image after hydrochloric acid vapor treatment for 24 hours. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Embodiment 1 A method for preparing polycrystalline alumina fiber comprises the following steps: S1, take 50g of crystalline aluminum chloride, add 350mL of deionized water and mix well, then add a mixed solution of 5g of aluminum powder, 8.3g of tartaric acid, 3.5g of nitric acid and 10g of lactic acid, place under reflux at 85°C for 3h, and obtain a polyaluminum chloride mother solution; S2, 3g of basic zirconium carbonate, 2.2g of glacial acetic acid and 10g of ethanol were mixed evenly to obtain a zirconium-containing solution, the polyaluminium chloride mother solution, the zirconium-containing solution and 5.8g of tetraethyl orthosilicate were mixed evenly, and then 3.5g of a fiber-forming aid polyvinyl pyrrolidone was added, and the mixture was concentrated by vacuum distillation to a viscosity of 60Pa·s to obtain a spinning colloid; S3, spinning colloid by centrifugal spinning machine, spinning colloid under the centrifugal force and hot air flow secondary traction to form fiber blank, and collected by fiber hood, spinning disk diameter 12cm, height 3cm, side wall drilled with three rows of 0.5mm diameter circular holes, the hole interval up and down left and right are 2mm, spinning disk speed 6000r / min, fiber hood temperature controlled at 60 ℃, relative humidity 40%; S4. After the fiber blank is dried, it is heat-treated by heating it to 500°C at a rate of 1°C / min, keeping it warm for 0.5h, then heating it to 650°C at a rate of 4°C / min, keeping it warm for 0.5h, then heating it to 1300°C at a rate of 6°C / min, keeping it warm for 1h, and using chemical vapor deposition to deposit a boron nitride nanolayer on the surface of the alumina fiber after heat treatment and sintering, with boron trichloride and ammonia as reaction gas sources, argon as carrier gas and dilution gas, with ammonia flow rate of 60mL / min, boron trichloride flow rate of 20mL / min and argon flow rate of 100mL / min, reaction system pressure of 5KPa, deposition temperature of 950°C, deposition time of 60min, to prepare polycrystalline alumina fiber.
[0021] See also Figure 1 , a is the SEM image after 150℃ water vapor treatment for 24h, b is the SEM image after sodium nitrite alkaline vapor treatment for 24h, c is the SEM image after hydrochloric acid vapor treatment for 24h. After the polycrystalline alumina fiber is exposed to water vapor, alkaline vapor and acid vapor, the fiber morphology of the sample remains intact, the surface morphology is smooth, and there are no obvious cracks or holes, indicating that the sample fiber has good acid and alkali resistance.
[0022] Embodiment 2 A method for preparing polycrystalline alumina fiber comprises the following steps: S1, take 50g of crystalline aluminum chloride, add 350mL of deionized water and mix well, then add a mixed solution of 5g of aluminum powder, 11.1g of tartaric acid, 3.5g of nitric acid and 11.7g of lactic acid, place under reflux at 85°C for 3h to obtain a polyaluminum chloride mother solution; S2, 2.5g of basic zirconium carbonate, 2.4g of glacial acetic acid and 9.2g of ethanol were mixed evenly to obtain a zirconium-containing solution, the polyaluminium chloride mother solution, the zirconium-containing solution and 7.7g of tetraethyl orthosilicate were mixed evenly, and then 3.5g of a fiber-forming aid polyvinyl pyrrolidone was added, and the mixture was concentrated by vacuum distillation to a viscosity of 50Pa·s to obtain a spinning colloid; S3, spinning colloid by centrifugal spinning machine, spinning colloid under the centrifugal force and hot air flow secondary traction to form fiber blank, and collected by fiber hood, spinning disk diameter 12cm, height 3cm, side wall drilled with three rows of 0.5mm diameter circular holes, the hole interval up and down left and right are 2mm, spinning disk speed 6000r / min, fiber hood temperature controlled at 60 ℃, relative humidity 40%; S4. After the fiber blank is dried, it is heat treated by heating it to 550°C at a rate of 1°C / min, keeping it warm for 0.5h, then heating it to 720°C at a rate of 5°C / min, keeping it warm for 1h, then heating it to 1300°C at a rate of 8°C / min, keeping it warm for 1.5h, and using chemical vapor deposition to deposit a boron nitride nanolayer on the surface of the alumina fiber after heat treatment and sintering, with boron trichloride and ammonia as reaction gas sources, argon as carrier gas and dilution gas, with ammonia flow rate of 60mL / min, boron trichloride flow rate of 20mL / min and argon flow rate of 100mL / min, reaction system pressure of 5KPa, deposition temperature of 950°C, deposition time of 60min, to prepare polycrystalline alumina fiber.
[0023] Embodiment 3 A method for preparing polycrystalline alumina fiber comprises the following steps: S1, take 50g of crystalline aluminum chloride, add 350mL of deionized water and mix well, then add a mixed solution of 5g of aluminum powder, 13.5g of tartaric acid, 3.8g of nitric acid and 10.8g of lactic acid, place under reflux at 85°C for 3h to obtain a polyaluminum chloride mother solution; S2, taking 2.7g of basic zirconium carbonate, 2.5g of glacial acetic acid and 10g of ethanol and mixing them evenly to obtain a zirconium-containing solution, mixing the polyaluminium chloride mother liquor, the zirconium-containing solution and 9.6g of tetraethyl orthosilicate evenly, then adding 5g of a fiber-forming aid polyvinyl pyrrolidone, and concentrating by vacuum distillation to a viscosity of 80Pa·s to obtain a spinning colloid; S3, spinning colloid by centrifugal spinning machine, spinning colloid under the centrifugal force and hot air flow secondary traction to form fiber blank, and collected by fiber hood, spinning disk diameter 12cm, height 3cm, side wall drilled with three rows of 0.5mm diameter circular holes, the hole interval up and down left and right are 2mm, spinning disk speed 6000r / min, fiber hood temperature controlled at 60 ℃, relative humidity 40%; S4. After the fiber blank is dried, it is heat treated by heating it to 550°C at a rate of 2°C / min, keeping it warm for 1 hour, then heating it to 800°C at a rate of 5°C / min, keeping it warm for 1 hour, and then heating it to 1300°C at a rate of 10°C / min, keeping it warm for 1 hour. A boron nitride nanolayer is deposited on the surface of the alumina fiber after heat treatment and sintering by chemical vapor deposition, with boron trichloride and ammonia as reaction gas sources, argon as carrier gas and dilution gas, with ammonia flow rate of 60mL / min, boron trichloride flow rate of 20mL / min and argon flow rate of 100mL / min, reaction system pressure of 5KPa, deposition temperature of 950°C, and deposition time of 60min, to prepare polycrystalline alumina fiber.
[0024] Comparative Example 1 A method for preparing polycrystalline alumina fiber comprises the following steps: S1. Take 50g of crystalline aluminum chloride and add 350mL of deionized water to mix evenly, then add 5g of aluminum powder and stir to mix, place under reflux at 85°C for 3h to obtain a polyaluminum chloride mother solution; S2, 3g of basic zirconium carbonate, 2.2g of glacial acetic acid and 10g of ethanol were mixed evenly to obtain a zirconium-containing solution, the polyaluminium chloride mother solution, the zirconium-containing solution and 5.8g of tetraethyl orthosilicate were mixed evenly, and then 3.5g of a fiber-forming aid polyvinyl pyrrolidone was added, and the mixture was concentrated by vacuum distillation to a viscosity of 60Pa·s to obtain a spinning colloid; S3, spinning colloid by centrifugal spinning machine, spinning colloid under the centrifugal force and hot air flow secondary traction to form fiber blank, and collected by fiber hood, spinning disk diameter 12cm, height 3cm, side wall drilled with three rows of 0.5mm diameter circular holes, the hole interval up and down left and right are 2mm, spinning disk speed 6000r / min, fiber hood temperature controlled at 60 ℃, relative humidity 40%; S4. After the fiber blank is dried, it is heat-treated by heating it to 500°C at a rate of 1°C / min, keeping it warm for 0.5h, then heating it to 650°C at a rate of 4°C / min, keeping it warm for 0.5h, then heating it to 1300°C at a rate of 6°C / min, keeping it warm for 1h, and using chemical vapor deposition to deposit a boron nitride nanolayer on the surface of the alumina fiber after heat treatment and sintering, with boron trichloride and ammonia as reaction gas sources, argon as carrier gas and dilution gas, with ammonia flow rate of 60mL / min, boron trichloride flow rate of 20mL / min and argon flow rate of 100mL / min, reaction system pressure of 5KPa, deposition temperature of 950°C, deposition time of 60min, to prepare polycrystalline alumina fiber.
[0025] Comparative Example 2 A method for preparing polycrystalline alumina fiber comprises the following steps: S1, take 50g of crystalline aluminum chloride, add 350mL of deionized water and mix well, then add a mixed solution of 5g of aluminum powder, 8.3g of tartaric acid, 3.5g of nitric acid and 10g of lactic acid, place under reflux at 85°C for 3h, and obtain a polyaluminum chloride mother solution; S2, the polyaluminium chloride mother liquor and 5.8g of tetraethyl orthosilicate were mixed evenly, and then 3.5g of a fiber-forming aid polyvinyl pyrrolidone was added, and the mixture was concentrated by vacuum distillation to a viscosity of 60Pa·s to obtain a spinning colloid; S3, spinning colloid by centrifugal spinning machine, spinning colloid under the centrifugal force and hot air flow secondary traction to form fiber blank, and collected by fiber hood, spinning disk diameter 12cm, height 3cm, side wall drilled with three rows of 0.5mm diameter circular holes, the hole interval up and down left and right are 2mm, spinning disk speed 6000r / min, fiber hood temperature controlled at 60 ℃, relative humidity 40%; S4. After the fiber blank is dried, it is heat-treated by heating it to 500°C at a rate of 1°C / min, keeping it warm for 0.5h, then heating it to 650°C at a rate of 4°C / min, keeping it warm for 0.5h, then heating it to 1300°C at a rate of 6°C / min, keeping it warm for 1h, and using chemical vapor deposition to deposit a boron nitride nanolayer on the surface of the alumina fiber after heat treatment and sintering, with boron trichloride and ammonia as reaction gas sources, argon as carrier gas and dilution gas, with ammonia flow rate of 60mL / min, boron trichloride flow rate of 20mL / min and argon flow rate of 100mL / min, reaction system pressure of 5KPa, deposition temperature of 950°C, deposition time of 60min, to prepare polycrystalline alumina fiber.
[0026] Comparative Example 3 A method for preparing polycrystalline alumina fiber comprises the following steps: S1, take 50g of crystalline aluminum chloride, add 350mL of deionized water and mix well, then add a mixed solution of 5g of aluminum powder, 8.3g of tartaric acid, 3.5g of nitric acid and 10g of lactic acid, place under reflux at 85°C for 3h, and obtain a polyaluminum chloride mother solution; S2, 3g of basic zirconium carbonate, 2.2g of glacial acetic acid and 10g of ethanol were mixed evenly to obtain a zirconium-containing solution, the polyaluminium chloride mother solution, the zirconium-containing solution and 5.8g of tetraethyl orthosilicate were mixed evenly, and then 3.5g of a fiber-forming aid polyvinyl pyrrolidone was added, and the mixture was concentrated by vacuum distillation to a viscosity of 60Pa·s to obtain a spinning colloid; S3, spinning colloid by centrifugal spinning machine, spinning colloid under the centrifugal force and hot air flow secondary traction to form fiber blank, and collected by fiber hood, spinning disk diameter 12cm, height 3cm, side wall drilled with three rows of 0.5mm diameter circular holes, the hole interval up and down left and right are 2mm, spinning disk speed 6000r / min, fiber hood temperature controlled at 60 ℃, relative humidity 40%; S4. After the fiber blank is dried, it is heat treated by heating it to 500°C at a rate of 1°C / min, keeping it warm for 0.5h, then heating it to 650°C at a rate of 4°C / min, keeping it warm for 0.5h, and then heating it to 1300°C at a rate of 6°C / min, keeping it warm for 1h to prepare polycrystalline alumina fiber.
[0027] Performance Testing The polycrystalline alumina fibers prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing: Referring to GB / T31290-2014 and ASTM C1557-14, the single-filament tensile test of continuous alumina fibers was performed using the XS (08) XT-3 single-fiber tensile testing machine of Shanghai Xusai Company, and at least 20 samples were tested for each group of fibers. The tensile strength of the fiber was calculated by the following formula:
[0028] Where: σ-average tensile strength of single fiber, unit MPa; F-maximum tensile force when fiber breaks, unit N; S-cross-sectional area of fiber, unit m 2 ; d-fiber diameter, unit: m; The thermal conductivity of the sample at 25°C was measured by the Hot Disk method; The fiber specific surface area was tested by the ASAP2000 specific surface area tester, and the data results are shown in Table 1.
[0029] Table 1 Test results of sample performance
[0030] It can be seen from the data in Table 1 that the thermal conductivity of the polycrystalline alumina fiber prepared in Examples 1-3 of the present invention at a high temperature of 1300°C is 0.03 W˙m -1 ˙K -1 The fiber has good high temperature resistance and heat insulation performance, the average tensile strength of the single fiber is greater than 660 MPa, it has good mechanical properties, and the micropore size of the fiber is generally maintained at a low level. In Comparative Example 1, a mixed solution of tartaric acid, nitric acid and lactic acid is not added as a spinning aid, in Comparative Example 2, a zirconium-containing solution is not added, and in Comparative Example 3, a boron nitride nanolayer is not deposited. The high temperature resistance and heat insulation performance and mechanical properties of Comparative Examples 1-3 are poorer than those of Examples 1-3.
[0031] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0032] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing polycrystalline alumina fiber, characterized in that: The following steps are involved: S1. Take crystalline aluminum chloride and add deionized water to mix evenly, then add a mixed solution of aluminum powder, tartaric acid, nitric acid and lactic acid, heat and reflux at 80-100°C for 2-4h to obtain a polyaluminum chloride mother liquor; S2, mixing basic zirconium carbonate, glacial acetic acid and ethanol evenly to obtain a zirconium-containing solution, mixing the polyaluminium chloride mother solution, the zirconium-containing solution and tetraethyl orthosilicate evenly, then adding a fiber-forming aid, and concentrating by vacuum distillation to obtain a spinning colloid; S3, spinning the spinning colloid by centrifugal spinning machine, the spinning colloid forms fiber blanks under the secondary traction of centrifugal force and hot air flow, and the fiber blanks are collected by a fiber forming hood; S4. After the fiber blank is dried, it is heat-treated, and a boron nitride nanolayer is deposited on the surface of the heat-treated and sintered alumina fiber using a chemical vapor deposition method to prepare the polycrystalline alumina fiber.
2. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: The molar ratio of the aluminum powder, tartaric acid, lactic acid, nitric acid and tetraethyl orthosilicate is 1:0.3-0.5:0.6-0.7:0.3-0.4:0.15-0.
3.
3. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: The mass ratio of basic zirconium carbonate, glacial acetic acid and ethanol is 2.5~3:2~2.5:7~10.
4. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: The fiber-forming auxiliary agent is polyvinyl pyrrolidone.
5. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: The viscosity of the spinning colloid is 40-80 Pa·s.
6. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: The specific process parameters of the heat treatment are: heating to 500-550°C at a rate of 1-3°C / min, keeping warm for 0.5-1h, then heating to 600-800°C at a rate of 3-5°C / min, keeping warm for 0.5-1h, then heating to 1000-1400°C at a rate of 5-10°C / min, keeping warm for 1-1.5h.
7. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: The process parameters of the chemical vapor deposition method are as follows: boron trichloride and ammonia are used as reaction gas sources, argon is used as carrier gas and dilution gas, the flow rate ratio of ammonia, boron trichloride and argon is 2~3:1:4~5, the pressure of the reaction system is 4~6KPa, the deposition temperature is 950~1050℃, and the deposition time is 45~60min.
8. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: During the centrifugal spinning process in step S3, the spinning disk rotates at a speed of 5000-6000 r / min.
9. The method for preparing polycrystalline alumina fiber according to claim 1, characterized in that: The temperature in the fiber-forming hood is controlled at 50~70℃ and the relative humidity is 30~50%.
10. A polycrystalline alumina fiber, made by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation process of multi-element composite alumina-based continuous fibers
CN102070326A
Preparation method of electrostatic spinning colloidal liquid for preparation of aluminum oxide ultrafine fibers
CN103396100A
Method for manufacturing ceramic matrix composite boron nitride interface coating
CN105463403A
Method for obtaining hollow aluminum oxide heat-insulation fibers by utilizing mudar fiber
CN106747359A
Sol-gel preparing and spinning method of ultrafine continuous alumina fibers
CN110922170A